Research handbook on representative shareholder litigation - Griffith, Sean J.; Erickson, Jessica; Webber, David (David H.); Winship, Verity; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2018)
Written by leading scholars and judges, the Research Handbook on Representative Shareholder Litigation is a modern-day survey of the state of this essential field. The book is an important and timely contribution by leading corporate law scholars, judges, and practitioners, seeking to better understand and explain the proliferation of shareholder litigation across the globe. It provides a cross-jurisdictional survey of litigation and empirical evidence on the recent evolution of these lawsuits, including in-depth analyses of several key forms of shareholder litigation. Its chapters cover securities class actions, merger litigation, derivative suits, and appraisal litigation, as well as other forms of shareholder litigation. Through in-depth analysis of these different forms of litigation, the book explores the agency costs inherent in representative litigation, the challenges of multijurisdictional litigation and disclosure-only settlements, and the rise of institutional investors. It also surveys how related issues are addressed across the globe, with a special focus on parallel forms of litigation in the United States, Canada, the United Kingdom, the European Union, Israel and China. This Research Handbook will be an invaluable resource on this important topic for scholars of corporate law, practitioners, judges, and legislators.
Part I Securities class actions -- 1. The development of securities litigation as a lawmaking partnership / Jill E. Fisch -- 2. Securities class actions and severe frauds / James J. Park -- 3. The shifting raison d'être of the rule 10b-5 private right of action / Amanda Marie Rose, -- Part II Shareholder derivative suits -- 4. The (un)changing derivative suit / Jessica Erickson -- 5. Claim character and class conflict in securities litigation / Richard A. Booth -- 6. Illegality and the business judgment rule / Charles R. Korsmo -- Part III Merger litigation -- a. Managing multijurisdictional litigation -- 7. Fighting frivolous litigation in a multijurisdictional world / Adam Badawi -- 8. Addressing the "baseless" shareholder suit: mechanisms and consequences / James D. Cox -- 9. Who collects the deal tax, where, and what Delaware can do about it / Sean J. Griffith and Anthony Rickey ---10. Forum shopping in the bargain aisle: Wal-Mart and the role of adequacy of representation in shareholder litigation / Lawrence A. Hamermesh and Jacob J. Fedechko -- 11. Limiting litigation through corporate governance documents / Ann M. Lipton -- b. Judicial perspectives on shareholder litigation -- 12. Disclosure settlements in the state courts post-trulia: practical considerations / James L. Gale -- 13. Changing attitudes: the stark results of thirty years of evolution in Delaware M&a litigation / J. Travis Laster -- 14. Appraisal rights in complete tender offers in Israel - a look into Israeli case-law / Ruth Ronnen -- c. Appraisal actions -- 15. Recent developments in stockholder appraisal / Charles R. Korsmo and Minor Myers -- 16. Appraisal as representative litigation / Minor Myers -- Part IV Litigants and lawfirms -- a. Plaintiffs and lawfirms -- 17. Lead plaintiffs and their lawyers: mission accomplished, or more to be done? / Stephen J. Choi and A.C. Pritchard ---18. The mimic-the-market method of regulating common fund fee awards: a status report on securities fraud class actions / Charles Silver -- 19. What do we know about law firm quality in m&a litigation? / Steven Davidoff Solomon and Randall S. Thomas -- b. Officers and directors -- 20. Jurisdiction over directors and officers in Delaware / Eric A. Chiappinelli -- 21. Stockholder litigation, fiduciary duties, and the officer dilemma / Megan Wischmeier Shaner -- Part V Comparative and international shareholder litigation -- a. The globalization of shareholder litigation -- 22. The globalization of entrepreneurial litigation: law, culture, and incentives / John C. Coffee, Jr. -- 23. The Teva case: A tale of a race to the bottom in global securities regulation / Sharon Hannes and Ehud Kamar -- b. Comparative shareholder litigation -- 24. A transatlantic perspective on shareholder litigation in public takeovers / Dan Awrey and Blanaid Clarke ---25. Private ordering of shareholder litigation in the EU and the US / Matteo Gargantini and Verity Winship -- 26. Mapping types of shareholder lawsuits across jurisdictions / Martin Gelter -- 27. Securities class actions in Canada: 10 years later / Poonam Puri -- c. Other modes of enforcement -- 28. CSRC enforcement of securities laws: preliminary empirical findings / Chao Xi -- Index.
Obsahuje bibliografie, bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: akcionáři; soudní spory; stockholders; lawsuits; e-knihy online; e-books online